Pengaruh Kepemimpinan Transformasional, Komunikasi Organisasi, Dan Kompensasi Finansial Terhadap Kinerja Karyawan PT. Hasta Prajatama - M. Surya Fransisco Abdillah; Sumartik Sumartik (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to analyze the influence of transformational leadership, organizational communication, and financial compensation on employee performance at PT Hasta Prajatama. This research uses a quantitative approach with an explanatory research method. The population in this study consists of employees of PT Hasta Prajatama, with a total sample of 120 respondents obtained through random sampling technique. Data were collected through questionnaires using a Likert scale, while the data analysis technique used multiple linear regression analysis with the help of SPSS software. The results show that transformational leadership, organizational communication, and financial compensation partially and simultaneously have a positive and significant effect on employee performance. Organizational communication is the most dominant variable influencing employee performance. Therefore, the company needs to strengthen inspirational leadership, improve effective organizational communication, and provide fair financial compensation to enhance employee performance and support the successful completion of company projects.